Sintesis Fly Ash Yang Diimpregnasi Dengan Na2O Sebagai Katalis Pada Proses Transesterifikasi Minyak Sawit Off-Grade Menjadi Biodiesel - S, Prasetyo Arva; Helwani, Zuchra; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Biodiesel is one of renewable energy in Indonesia that have to be development. Biodiesel formed as liquid fuel and has same property with petrodiesel. Biodiesel can be synthesized from off-grade palm oil using Na2O/fly ash as catalyst in transesterification process. Employing fly ash as support in Na2O has a good impact due to provide wide surface of catalyst. In this study aims to see the influence of reaction temperature, molar ratio of methanol and oil and concentration of Na2O/fly ash towards biodiesel yield. The process was conducted through reaction of esterification and followed by transesterification reaction. Processing of the data in this study was conducted by response surface methodology (RSM) using Design Expert 7.0 program which is experimental design determined by central composite design (CCD) which consists of three variables. The highest result of biodiesel yield was 81,2% at 60oC reaction temperature, molar ratio of methanol : oil 8 : 1 and catalyst concentration of Na2O/fly ash 4%-wt. Biodiesel characteristics such as density, kinematic viscosity, acid value and flash point has been appropriate by Indonesian biodiesel standard. The most significant condition of process affecting the yield of biodiesel was catalyst concentration.Keywords : biodiesel, catalyst, fly ash, off-grade palm oil, transesterification